The Hidden Psychology of Social Networks - Federer, Joe (McGraw Hill-Ascent Audio, 2021)
Leading marketing practitioner and thought leader Joe Federer draws on evolutionary biology, anthropology, neuroanatomy, and psychology, as well as more than a decade of hands-on experience, to explain why people act so differently in various online spaces and what they are seeking from participating in each one. With a framework based on Freud's Id, Ego, and Superego model of the human psyche, he demonstrates how the internet is a digital reflection of the collective human psyche and how different social networks correspond to different mindsets: platforms like Reddit to the unfiltered Id, Facebook and Twitter to the managed Ego, and Instagram to the ideal Superego. In the same way you behave differently when you're home alone, out with friends, communicating with family, or interacting with coworkers, people act and express themselves differently in these various online spaces. Context matters. Understanding this will enable you to develop and execute effective engagement strategies to reach your target audiences on each social network. Learn: how to create content that drives sharing and word-of-mouth; how brands can fit natively into different types of social channels; how to balance branded social presences across different networks; and why authenticity will only grow in importance to consumers.
Online resource; Title from title page (viewed June 29, 2021)
Keywords: Livres numériques; Audiobooks